Joselito® and lowering of LDL‐cholesterol concentration, blood pressure, and reduction of coronary heart disease risk: Evaluation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006 - EFSA Panel on Nutrition, Novel Foods and Food allergens (NDA); Dominique Turck; Torsten Bohn; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Helle Katrine Knutsen; Alexandre Maciuk; Inge Mangelsdorf; Harry J. McArdle; Androniki Naska; Kristina Pentieva; et al. (EFSA Journal)
Abstract Following an application from Cárnicas Joselito S.A. pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of Spain, the Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to ‘Joselito ham increases antioxidant substances in the body, reduces blood pressure and plasma triglycerides, decreases oxidative stress and prevents effect in diseases related to the cardiovascular and intestinal systems’. The scope of the application was proposed to fall under a health claim referring to disease risk reduction. The food constituent that is the subject of the health claim is Joselito, an Iberian ham characterised by a high content of oleic acid. The Panel considers that the food is sufficiently characterised. The Panel considers that lowering of LDL‐cholesterol concentration and blood pressure is a beneficial effect by decreasing the risk of coronary heart disease. Upon a request from EFSA, the applicant identified one human intervention study as being pertinent to the claim. However, due to methodological limitations, the Panel considers that no conclusions can be drawn from this study for the scientific substantiation of the claim. The Panel notes that no human intervention studies from which conclusions could be drawn for the scientific substantiation of the claim were provided by the applicant. The Panel concludes that a cause and effect relationship has not been established between the intake of Joselito® ham and the reduction of LDL‐cholesterol concentration or blood pressure.